PENGARUH MEDIA ANIMASI BERBASIS ADOBE FLASH TERHADAP HASIL BELAJAR PADA MATERI PLANTAE - Herlinda, Herlinda; Hardigaluh, Basuki; Ariyati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to determine effect adobe flash based animation media toward student assesment at material plantae in class X SMA Mujahidin Pontianak. The research was a Quasy Experimental Design with Nonequivalent control group design. The sample of this research are X MIA 1 as experiment class and X MIA 2 as control class. The sampling technique is by saturated sampling. The instrument been used was multiple choice test that consists of 20 items. Average student assesment that had been animation media based adobe flash 15,55 was higher by those using power point 13,37. The t test obtained t obtained > t table Â (3,52> 1,67), meaning that there were significant differences between students assesment that taught by adobe flash based animation media and power point. The conclusion was that learning by using animation media based on adobe flash can increase studentâ€™s learning outcomes in material plantae.Â Keywords: Adobe Flash Based Animation Media, Material Plantae.